Martket Market Share Analysis and Forcasting Export Trend of Indonesian Palm Oil: Response to Trade War 2025 - Fitri, Febti Aulia; Hidayanti, Anna Apriana; Setiawan, Rifani Nur Sindy (ITScience (Information Technology and Science), 2025)
The tariff war between the US and China in 2025 is a signal for Indonesia as the world's largest palm oil exporter that relies on both markets. Market diversification needs to be carried out to avoid instability and uncertain conditions. This study aims to analyze market share through the competitiveness of palm oil in 5 main export destination countries. The EPD method is used with secondary data from 2013-2023. After identifying the countries with the most potential for market penetration, the forecast of the value of Indonesian palm oil exports to these countries was carried out using the ARIMA method with monthly secondary data from January 2013 to May 2023. The EPD analysis results show that Pakistan has the highest Rising Star position, which means it has the greatest potential to be used as a destination for Indonesian palm oil exports. Meanwhile, the results of the ARIMA modelling found that the most appropriate forecasting model was ARIMA (1,1,1) without a constant. As a result, the forecast of the value of Indonesian palm oil exports to Pakistan shows a significant upward trend of 0.4% per month. This study found that the Pakistani market could be used as an export destination to diversify the market and, simultaneously, as an entry point to surrounding countries to prioritize the sustainability of the Indonesian palm oil trade.